Power-force-velocity profiling as a function of used loads and task experience - Fessl, I.; Wiesinger, H. P.; Kröll, J. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To evaluate cohort-specific reliability and concurrent validity of 3 different vertical power-force-velocity (P-F-v) profiles to determine force, velocity, maximal power, and the slope of the force-velocity relationship using squat jumps.